2013
DOI: 10.2147/opth.s46283
|View full text |Cite
|
Sign up to set email alerts
|

Surgical therapy versus observation for lamellar macular hole: a retrospective comparison study

Abstract: BackgroundThe purpose of this study was to compare anatomic and visual changes in patients with lamellar macular hole undergoing pars plana vitrectomy with those in patients undergoing follow-up only.MethodsIn this retrospective consecutive case series study, we evaluated two groups of eyes, comprising 19 eyes from 19 patients with lamellar macular hole who underwent pars plana vitrectomy with internal limiting membrane peeling and 21 eyes from 21 patients with lamellar macular hole who had follow-up only. Cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…Moreover, some authors have reported no visual improvement in LMH after surgery (8,14,15), which supports the degenerative hypothesis. However, there is increasing evidence that surgery may also be beneficial for patients with LMH (9)(10)(11)(12)(13)(14)(15)(16). This raises speculation regarding the true degenerative nature of LMH, since it remains to be understood whether a condition that can improve after surgery, and in most cases does not recur, can be defined as "degenerative.…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…Moreover, some authors have reported no visual improvement in LMH after surgery (8,14,15), which supports the degenerative hypothesis. However, there is increasing evidence that surgery may also be beneficial for patients with LMH (9)(10)(11)(12)(13)(14)(15)(16). This raises speculation regarding the true degenerative nature of LMH, since it remains to be understood whether a condition that can improve after surgery, and in most cases does not recur, can be defined as "degenerative.…”
mentioning
confidence: 73%
“…Some previous studies have reported that LMH appears to be associated with worse outcomes after surgery (14,15), supporting the degenerative hypothesis, while others have found surgery to be beneficial for eyes showing disease progression (17,18). However, there are many discrepancies between these studies, preventing definitive conclusions.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…On the other hand, it could be conservatively concluded that a select group of patients with symptomatic LMHs and significant epiretinal traction may benefit from surgery. Nevertheless, it should be mentioned to the patient that up to 20% of patients undergoing vitrectomy for LMHs experience significant visual loss,28 and after surgery, the occurrence of a full-thickness macular lesion is not uncommon in these patients 27,28,35,36,39,40. LMHs are an extremely interesting condition where intraretinal and epiretinal forces play a unique role.…”
Section: Resultsmentioning
confidence: 99%
“…Mean BCVA improved from 0.54 to 0.33 logMAR in the operated group and decreased from 0.51 to 0.55 logMAR in the control group. Two eyes developed FTMHs after surgery 40. Parolini et al performed vitrectomy with ERM/ILM peeling in 19 eyes.…”
Section: Surgical Strategiesmentioning
confidence: 99%